Si/Al derived opal concentrations of IODP Site U1537 - Moritz Hallmaier; Marcus Gutjahr; Jörg Lippold; Sidney R Hemming; Lukas Gerber; Michael E Weber; Anton Eisenhauer (PANGAEA, 2025)
We calculated the opal content by normalizing XRF based Si/Al-ratios with FTIRS based biogenic opal measurements. This shows a much stronger correlation (R=0.96) for the last 300 kyr than b* and opal content (R=0.77) (Weber et al. 2022).
In: Hallmaier, M et al. (2025): Authigenic Uranium Preservation and Bottom Water Oxygenation in the Scotia Sea [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982959